The remarkable outburst of the highly evolved post-period-minimum dwarf nova SSS J122221.7-311525 - V. V. Neustroev; R. R. Marsh; S. V. Zharikov; C. Knigge; E. Kuulkers; J. P. Osborne; K. L. Page; D. Steeghs; V. F. Suleimanov; G. Tovmassian; E. Breedt; A. Frebel; et al. (OXFORD UNIV PRESS, 2022)
We report extensive 3-yr multiwavelength observations of the WZ Sge-type dwarf nova SSS J122221.7-311525 during its unusual double superoutburst, the following decline and in quiescence. The second segment of the superoutburst had a long duration of 33 d and a very gentle decline with a rate of 0.02 mag d(-1), and it displayed an extended post-outburst decline lasting at least 500 d. Simultaneously with the start of the rapid fading from the superoutburst plateau, the system showed the appearance of a strong near-infrared excess resulting in very red colours, which reached extreme values (B -I similar or equal to 1.4) about 20 d later. The colours then became bluer again, but it took at least 250 d to acquire a stable level. Superhumps were clearly visible in the light curve from our very first time-resolved observations until at least 420 d after the rapid fading from the superoutburst. The spectroscopic and photometric data revealed an orbital period of 109.80 min and a fractional superhump period excess less than or similar to 0.8 per cent, indicating a very low mass ratio q less than or similar to 0.045. With such a small mass ratio the donor mass should be below the hydrogen-burning minimum mass limit. The observed infrared flux in quiescence is indeed much lower than is expected from a cataclysmic variable with a nearmain- sequence donor star. This strongly suggests a brown-dwarf-like nature for the donor and that SSS J122221.7-311525 has already evolved away from the period minimum towards longer periods, with the donor now extremely dim.